2009
DOI: 10.1086/605896
|View full text |Cite
|
Sign up to set email alerts
|

Altered Nucleotide Receptor Expression in a Murine Model of Cerebral Malaria

Abstract: In cerebral malaria, the most severe complication of malaria, both neurotransmission mechanisms and energy metabolism are affected. To understand how metabolic changes modify neurotransmission, we examined P2 receptor expression in a murine model of cerebral malaria. Quantitative polymerase chain reaction experiments revealed that parasite deposition was greatest in the cerebellum, compared with other areas of the brain, suggesting a correlation between brain parasitemia and loss of control of movement. Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Real-time PCR was conducted with SYBR Green (Roche) on a MyiQ Real-Time PCR System (Bio-Rad). The TaqMan probes for mouse EP1, EP2, EP3, EP4, P2Y2, and P2Y4 used in this study were purchased from Applied Biosystems and experiments for validation of amplification efficiency were performed for each TaqMan probe set [28, 29]. PCR thermocycling parameters were 95°C for 10 min, 40 cycles of 95°C for 15 s, and 60°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR was conducted with SYBR Green (Roche) on a MyiQ Real-Time PCR System (Bio-Rad). The TaqMan probes for mouse EP1, EP2, EP3, EP4, P2Y2, and P2Y4 used in this study were purchased from Applied Biosystems and experiments for validation of amplification efficiency were performed for each TaqMan probe set [28, 29]. PCR thermocycling parameters were 95°C for 10 min, 40 cycles of 95°C for 15 s, and 60°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…This decrease could lead to an alteration of P2Y6R functions and, consequently, of the related down stream pathways. In a very recent study concerning the expression of nucleotide receptors in a mouse model of cerebral malaria, it was observed that the expression of most P2 receptors was decreased in the thalamus‐hypothalamus of the brains of infected mice, suggesting a role for these receptors in the pathophysiology of cerebral malaria (Marin‐Garcia et al ., 2009). The expression level of P2Y6R was not evaluated in this murine malaria model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mammalian RBCs express ADORA2b and several P2Y and P2X receptors on their surface [ 85 ]. In experimental cerebral malaria the expression of several P2X and P2Y receptors is altered after P. berghei infection [ 86 ]. However, to date little is known about purinergic modulation of malaria-specific immune response.…”
Section: Parasitic Infectionsmentioning
confidence: 99%